Genomic analysis of Sinorhizobium meliloti LPU63, an acid-tolerant and symbiotically efficient alfalfa-nodulating rhizobia - Cafiero, Juan Hilario; Salvetti Casasco, María; Lozano, Mauricio Javier; Vacca, Carolina; López García, Silvina Laura; Draghi, Walter Omar; Lagares, Antonio; Del Papa, María Florencia (Frontiers in Agronomy, 2023)
The growth and persistence of alfalfa (Medicago sativa), a perennial legume capable of producing high yields of high-quality forage, is reduced in moderately acidic soils. The low performance of alfalfa at low pH is due to numerous factors that affect the host plant, their rhizobia, and the symbiotic interaction.Sinorhizobium meliloti LPU63 was isolated from acid topsoil (in Argentina) and showed to be a highly competitive and efficient N2-fixing rhizobium under both, neutral and moderately acidic soil conditions. In this study, we obtained a draft of the LPU63 genome sequence using Illumina HiSeq4000. The whole genome phylogenetic analysis confirmed the taxonomic position of LPU63 as a S. meliloti strain and the multilocus sequence analysis confirmed that LPU63 is not related to the strains used in Argentina in bioformulations. The genomic analysis showed that beyond the canonical chromosome, pSymA, and pSymB, LPU63 strain has an accessory plasmid that codes for a repABC origin of replication and a conjugative T4SS, suggesting that this plasmid could be self-transmissible. In addition, the complete denitrification pathway (i.e., the gene clusters nap, nir, nor, and nos), including napC and nosZ, which could be used as an alternative respiration route under hypoxic conditions with moderate N2O emissions was found. Also, genes associated with plant growth-promoting activities (PGPR) and the degradation of phenylacetic acid (PAA) were identified. LPU63 is a highly melanogenic strain, a property that could enhance its survival under soil conditions, and the genome data showed a particular arrangement of the genes involved in melanin production. The information regarding LPU63 activities compatible with plant-growth promotion phenotypes, together with other characteristics mentioned here (melanin production, potential moderate N2O emissions), constitute the basis of future experiments toward the rational design of a novel bioinoculant for the environmentally sustainable production of alfalfa.